Adolescent Metabolic Syndrome Risk Is Increased with Higher Infancy Weight Gain and Decreased with Longer Breast Feeding. (5th July 2012) - Khuc, Kim; Blanco, Estela; Burrows, Raquel; Reyes, Marcela; Castillo, Marcela; Lozoff, Betsy; Gahagan, Sheila
Abstract : Background . Prevalence of the metabolic syndrome is increasing in pediatric age groups worldwide. Meeting the criteria for the metabolic syndrome puts children at risk for later cardiovascular and metabolic disease. Methods . Using linear regression, we examined the association between infant weight gain from birth to 3 months and risk for the metabolic syndrome among 16- to 17-year-old Chilean adolescents (n = 357 ), accounting for the extent of breastfeeding in infancy and known covariates including gender, birth weight, and socioeconomic status. Results . Participants were approximately half male (51%), born at 40 weeks of gestation weighing 3.5 kg, and 48% were exclusively breastfed for ≥ 90 days. Factors independently associated with increased risk of metabolic syndrome in adolescence were faster weight gain in the first 3 months of life (B = 0.16, P < 0.05 ) and male gender (B = 0.24, P < 0.05 ). Breastfeeding as the sole source of milk for ≥ 90 days was associated with significantly decreased risk of metabolic syndrome (B = − 0.16 ). Conclusion . This study adds to current knowledge about early infant growth and breastfeeding and their long-term health effects.